Microcapsules of Poly(butylene adipate-co-terephthalate) (PBAT) Loaded with Aliphatic Isocyanates for Adhesive Applications - Aguiar, A (2024)
Thiswork introduces theencapsulationofhexamethylenediisocyanatederivatives(HDI,TriHDI, andPHDI)with thebiodegradablepolymerpoly(butyleneadipate-co-terephthalate) (PBAT) through a solvent evaporationmethod. Thesemicrocapsules(MCs)werethenemployedinadhesiveformulations for footwear.Moreover,MCs containingPHDIwereproduced ina closed vessel, demonstrating the potential for recovering and reusingorganicsolventsforthefirsttime.TheMCswereachieved withan isocyanatepayloadreachingupto68wt%, displayinga spherical shape, a core−shell structure, and thinwalls without holesorcracks.TheapplicationofMCsascross-linkingagentsfor adhesives was evaluated following industry standards. The adhesives’ strength surpassed theminimum requirement by a significantmargin.Creeptestsdemonstratedthat the formulationwithMCs exhibits superior thermostability. Furthermore, the formulationwithMCs-PHDIpresentedthebestresultsreportedtodateforthistypeofsystem,asnodisplacementwasobservedin thebondedsubstrates.EnvironmentalassessmentindicatesthatadhesiveswithMCshavehigherglobalwarmingpotential(+16.2%) andenergyconsumption(+10.8%)thanthestandardcommercialadhesives,butunderalternativerealisticscenarios, thedifferences canbe insignificant.Therefore, adhesive formulations incorporatingMCspromisetobeonparwithtraditional adhesivesystems regardingenvironmental impactswhileprovidingbenefitssuchasimprovedandsafehandlingof isocyanatesandexcellentbonding effectiveness.